TRANSFORMASI DIGITAL SEKOLAH UNTUK MENINGKATKAN ENGAGEMENT DI KB ISLAM ANAK NEGERI - Oktiarso, Teguh; Ekawati, Yurida; Susilowati, Meme; Putrianto, Novenda Kartika (Universitas Bunda Mulia, 2026)
KB Islam Anak Negeri Karangploso is an Islamic-based early childhood education institution that plays a role in shaping a generation with good character. However, this institution faces obstacles in utilising learning technology and managing social media, which has an impact on operational effectiveness and marketing strategies. This community service programme aims to support the school's digital transformation through two strategic steps: optimising social media and developing an integrated website. The approach used includes a needs survey, preparation of an implementation plan, implementation of a digital literacy training programme, and continuous evaluation. Social media optimisation focuses on creating educational and promotional content, while the website is developed as a school information centre. The results of these activities show an increase in the ability of educators to manage digital media and an increase in community involvement in school programmes. The implementation of these solutions is expected to strengthen the institution's image, expand the reach of information, and support the sustainability of digital transformation at KB Islam Anak Negeri Karangploso.